DETECTION AND EARLY INTERVENTION FOR SPECIAL NEEDS CHILDREN (SPEECH DELAY) - Liyanti, Yuni; yati, Rusmi; Ermawanti, Triandy (International Conferences on Early Childhood Education Proceedings, 2024)
Abstract: This study aims to understand speech delays in a student at TKIT Thoriq Al Fath using a qualitative method with three main stages: description, reduction, and selection. In the description stage, observations and interviews identified that Aurora Vanessa Zhita experiences a speech delay. The reduction stage highlights the lack of early detection programs in the school. In the selection stage, in-depth analysis emphasizes the importance of early intervention through observation and individual programs. Interview results indicate the need for professional assistance and collaboration between teachers, the school, and parents. Pretest results showed a 45% understanding of early detection, while posttest results showed an increase to 65%, indicating the effectiveness of the training program. This study emphasizes the importance of early detection, appropriate intervention, and collaboration to support the development of children with speech delays.